Kindred specters : death, mourning, and American affinity - Peterson, Christopher, 1972- (University of Minnesota Press, 2007)
Probing Derrida's notion of spectrality as well as Orlando Patterson's concept of social death, Christopher Peterson examines how death, mourning, and violence condition all kinship relations. Tracing the connections between kinship and mourning in American literature and culture, Peterson argues that socially dead others can be reanimated only if we avow the mortality and mourning that lie at the root of all kinship relations.